Polydatin Glycosides Improve Monocrotaline-Induced Pulmonary Hypertension Injury by Inhibiting Endothelial-To-Mesenchymal Transition - Chen, Xing; He, Yao; Yu, Zhijie; Zuo, Jianli; Huang, Yan; Ruan, Yi; Zheng, Xiaoyuan; Ma, Yu (Frontiers in Pharmacology, 2022)
Objective: To study the effect of polydatin on the injury of pulmonary arterial hypertension (PAH) induced by monocrotaline (MCT). Methods: SD rats were induced to develop PAH injury by a single subcutaneous injection of MCT (60 mg/kg). From the second day, rats in the administration group were orally given sildenafil (20 mg/kg) and polydatin (30 or 60 mg/kg) for 3 weeks. At the end of the experiment, right ventricular hypertrophy (RVH) index of SD rats was calculated, pathological damage was assessed by HE staining, transcription levels of target genes were detected by RT-PCR and Elisa, and expression levels of Endothelial-to-mesenchymal transition (EndMT) related proteins were detected by immunohistochemistry (IHC) and immunofluorescence (IF). Finally, molecular docking analysis was used to verify the interaction of polydatin on the main targets. Results: Polydatin could significantly restore the body function, reduce MCT-induced PAH injury, reduce serum biochemical indices; polydatin could effectively inhibit EndMT process by decreasing the expression of N-cadherin, β-catenin and vimentin; polydatin could down-regulate TAGLN expression and increase PECAM1 expression to reduce pulmonary vascular remodeling. The interaction between polydatin and EndMT target was confirmed by molecular docking operation. Conclusion: Pharmacological experiments combined with Combining molecular docking was first used to clarify that polydatin can reduce the pulmonary endothelial dysfunction and pulmonary vascular remodeling induced by MCT by inhibiting EndMT. The results of the study provide new ideas for the further treatment of PAH injury.